2008
DOI: 10.1038/jid.2008.155
|View full text |Cite
|
Sign up to set email alerts
|

All-Trans Retinoic Acid Shifts Propionibacterium acnes-Induced Matrix Degradation Expression Profile toward Matrix Preservation in Human Monocytes

Abstract: Propionibacterium acnes is a critical component in the pathogenesis of acne vulgaris, stimulating the production of various inflammatory mediators, such as cytokines and chemokines, important in the local inflammatory response found in acne. This study explored the role of P. acnes and its ability to induce matrix metalloproteinases (MMPs) in primary human monocytes and how this induction is regulated by retinoids. MMP-1- and MMP-9-expressing cells were present in perifollicular and dermal inflammatory infiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 30 publications
2
43
0
2
Order By: Relevance
“…We have also confirmed that gelatinolytic activity at approximately 92 kDa, which might correspond to proMMP-9, was negligible in sebocytes and dermal fibroblasts (data not shown). Since keratinocytes, monocytes, and dermal fibroblasts in hu-mans play important roles for MMP-mediated cutaneous ECM degradation in acne, 10,11,17,18) these results suggest that hamster sebocytes as well as dermal fibroblasts are useful for the investigation of sebaceous and pilosebaceous ECM remodeling in acne lesion.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…We have also confirmed that gelatinolytic activity at approximately 92 kDa, which might correspond to proMMP-9, was negligible in sebocytes and dermal fibroblasts (data not shown). Since keratinocytes, monocytes, and dermal fibroblasts in hu-mans play important roles for MMP-mediated cutaneous ECM degradation in acne, 10,11,17,18) these results suggest that hamster sebocytes as well as dermal fibroblasts are useful for the investigation of sebaceous and pilosebaceous ECM remodeling in acne lesion.…”
Section: Resultsmentioning
confidence: 98%
“…[13][14][15] We recently reported that P. acnes directly augments sebum production in hamster sebaceous glands in vivo and in vitro. 16) In addition, P. acnes has also been reported to augment the expression of proMMPs-1 and -9 in human monocytes 17) and that of proMMP-2 in human dermal fibroblasts. 18) However, it remains unclear whether or not P. acnes directly regulates MMP production in sebaceous glands that may be associated with the onset of scar formation in acne.…”
Section: )mentioning
confidence: 99%
“…Carotenoids, in particular β-carotene, have been shown to inhibit the synthesis and activation of MMP-9 in cell lines and mouse models [30][31][32]. Emerging evidence indicates that retinoids, the metabolically active derivatives of vitamin A, exhibit effects on vascular cells and have anti-inflammatory properties that may be [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…RA has been demonstrated to promote alveolarisation in a rat model [1], but other reports in rats and mice failed to demonstrate such an effect [2][3][4][5]. Furthermore, ATRA can improve the protease/anti-protease balance [6,7] and has anti-inflammatory activity [8]. Oral therapy with ATRA in chronic obstructive pulmonary disease (COPD) has been reported and there is evidence of some improvement [9,10].…”
Section: To the Editorsmentioning
confidence: 99%